Access to a tailored mobile application enhances medication adherence among young users of antidepressants - Larsen, Rønnaug Eline; Hole, Kristine; Selle, Maria Lie; Johannessen Landmark, Cecilie; Krogstad, Tonje; Holm, Lene Berge (Frontiers in Pharmacology, 2024)
Introduction: Patients' adherence to antidepressants is generally reported to be poor. This study examined whether users of selective serotonin reuptake inhibitors (SSRIs) and serotonin and norepinephrine reuptake inhibitors (SNRIs) enhance medication adherence following access to a mobile application (app) tailored for this patient group. The study addresses the implementation phase of medication adherence.The study was a single group pre-post intervention design. Data were collected using the validated OsloMet Adherence-to-medication Survey tool (OMAS-37) before and after app access.Pre-app access survey (Survey 1) was conducted via social media and online newspapers, encompassing 445 SSRI/SNRI users aged 18 years and above. Post-app access survey (Survey 2) was sent to 103 SSRI/SNRI users from Survey 1. Wilcoxon Signed Rank Test compared pre-and post-intervention adherence measurements. Pearson's chi-square tests and Fisher's exact tests compared study population categories.Results: Forty-two SSRI/SNRI users, median age 26 (IQR 17), 93% identifying as female, used the app while using the same antidepressant during the two-month period between gaining access to the app and Survey 2. There was a statistically significant reduction in non-adherence score post-app access (z=3.57, n=42, p<0.001) with medium effect size (r=0.39), indicating enhanced adherence.Total non-adherence score decreased by 39% from pre-to post-access, and there was a 12% decrease in users scoring equivalent with poor adherence (score <2) post-access. Twenty-nine of 37 nonadherence causes improved, with three showing statistical significance. Of 42 responders, 50% (n=21) indicated using the app one to two times, while 50 % (n=21) more than three times.Approximately 69% (n=28) found it useful, and 43% (n=18) felt safer in their use of antidepressants after access to the app. No significant preference was observed for the app over alternative sources of information.Enhanced medication adherence was observed among antidepressant users following access to the tailored app. Further studies are warranted to evaluate the app applicability to a broader range of antidepressants users or other patient groups, encompassing those in the initiation phase of medication adherence. The app is intended as an easily accessible supplement to the information and advice provided by prescribing physicians and dispensing pharmacists.